DETERMINANTS OF INCOME DIVERSIFICATION IN INDONESIAN ISLAMIC BANKS: AN ARDL APPROACH - Muhammad Deni Putra; Muhammad Dedat Dingkoroci Akasumbawa; Laelani Rukmana (I-Economics: A Research Journal on Islamic Economics)
The increasing competition and evolving regulatory landscape in the Islamic banking sector have prompted banks to diversify their income sources beyond traditional financing activities. This study investigates the determinants of income diversification in Indonesian Islamic banks by examining the influence of bank-specific and macroeconomic factors. The research is grounded in the need to enhance financial stability and sustainability in the dual banking system of Indonesia, where Islamic banks operate alongside conventional counterparts but face structural and operational limitations. The study employs the Autoregressive Distributed Lag (ARDL) approach using monthly panel data covering the period from January 2014 to February 2024.  The results indicate that in the short run, income diversification is significantly influenced by NPF and inflation, suggesting that risk and price instability reduce income diversification efforts. In the long run, ROA and exchange rate show a positive and significant relationship with income diversification, highlighting the importance of profitability and exchange rate stability. CAR and SIZE do not show significant influence in either the short or long run. This study contributes to the limited empirical research on income diversification in Islamic banks in emerging economies. It also offers policy insights by identifying factors that could support diversification strategies, which are crucial for improving competitiveness and resilience in the Islamic banking industry.